Acceptance of Post-Placental Intrauterine Contraceptive Device in Denpasar - Ni Made Rai Widiastuti; Ni Luh Putu Suariyani; I Nyoman Mangku Karmaya (Public Health and Preventive Medicine Archive, 2016)
Background and purpose: The Indonesian Demographic Health Survey of 2012 indicated that the prevalence of contraceptive use in Bali Province has decreased compared to 2007. In addition, the proportion of the use an intrauterine device (IUD) also continues to decline. To increase number of IUD acceptors is to promote postplacental intrauterine device (PPIUCD), however the acceptance remains low. This study aims to determine factors associated with acceptance of post-placental intrauterine device in Denpasar. Methods: Study was cross sectional with a total of 100 respondents selected by consecutive sampling. Respondents were mothers who had gave birth in January-February 2016 at Wangaya General Hospital and three health centers (Dauh Puri Sub Health Center, East Denpasar I and South Denpasar IV). Data were collected by interview in hospital and health center. Chi square test was conducted for bivariate analysis and multivariate using logistic regression. Results: Proportion of PPIUCD acceptance was 35%. Multivariate analysis indicated that PPIUCD acceptance was associated with perception of benefits (AOR=10.39; 95% CI: 2.792-38.56), perception of low side effects (AOR=5.288; 95%CI: 1.085-25.761), role of health workers (AOR=7.1; 95%CI: 1.781-28.60) and support of the husband (AOR=12.020; 95% CI=2.888-50.01). Conclusion: Variables associated with PPIUCD acceptance were perception of low side effects, perception